The effect of ALD-grown Al2O3 on the refractive index sensitivity of CVD gold-coated optical fiber sensors. (5th October 2015) - Mandia, David J; Zhou, Wenjun; Ward, Matthew J; Joress, Howie; Sims, Jeffrey J; Giorgi, Javier B; Albert, Jacques; Barry, Seán T
Abstract: The combined effect of nanoscale dielectric and metallic layers prepared by atomic layer deposition (ALD) and chemical vapor deposition (CVD) on the refractometric properties of tilted optical fiber Bragg gratings (TFBG) is studied. A high index intermediate layer made up of either 50 nm or 100 nm layers of Al2 O3 (refractive index near 1.62) was deposited by ALD and followed by thin gold layers (30–65 nm) deposited from a known single-source gold (I) iminopyrrolidinate CVD precursor. The fabricated devices were immersed in different surrounding refractive indices (SRI) and the spectral transmission response of the TFBGs was measured. Preliminary results indicate that the addition of the dielectric Al2 O3 pre-coating enhances the SRI sensitivity by up to 75% but this enhancement is highly dependent on the polarization and dielectric thickness. In fact, the sensitivity decreases by up to 50% for certain cases. These effects are discussed with support from TFBG simulations and models, by quantifying the penetration of the evanescently coupled light out of the fiber through the various coating layers. Additional characterization studies have been carried out on these samples to further correlate the optical behaviour of the coated TFBGs with the physical properties of the gold and Al2 O3 layers, using atomic force microscopy x-ray photoelectron spectroscopy and an ensemble of other optical and x-ray absorption spectroscopy techniques. The purity, roughness, and morphology of gold thin films deposited by CVD onto the dielectric-TFBG surface are also provided.